LEXICAL-SEMANTIC EXPRESSION OF EARLY YOUTH “JEUNESSE” IN UZBEK AND FRENCH (Scientific journal of the Fergana State University, 2023)
The article describes the lexico-semantic expression of early youth/jeunesse in Uzbek and French. The concept of "youth" in Uzbek is represented by more than 100 lexemes, including words belonging to different groups of words, different names of the described "period of youth," nouns that include the names of young people, as well as expressions of qualities, processes and actions related to the concept of "youth."